Psychological Fitness and Resilience A Review of Relevant Constructs, Measures, and Links to Well-Being - Robson, Sean (RAND Corporation, 2014)
This report is one of a series designed to support Air Force leaders in promoting resilience among its Airmen, civilian employees, and Air Force families. It examines the relationship between psychological fitness and resilience, using key constructs found in the scientific literature that address address self-regulation, positive affect, perceived control, self-efficacy, self-esteem, and optimism.